Effects of storage time prolongation on in vivo and in vitro characteristics of 4°C–stored platelets. Issue 3 (4th February 2020) - Stolla, Moritz; Bailey, S. Lawrence; Fang, Lydia; Fitzpatrick, Lynda; Gettinger, Irena; Pellham, Esther; Christoffel, Todd
ABSTRACT: BACKGROUND: Cold (4°C)‐stored platelets are currently under investigation for transfusion in bleeding patients. It is currently unknown how long cold‐stored platelets can be stored for clinical applications. STUDY DESIGN AND METHODS: Twenty three subjects were recruited. Twenty‐one subjects were available for in vivo assessment and received indium‐111 radiolabeled, cold‐stored platelets. We investigated 5‐ (n = 5), 10‐ (n = 6), 15‐ (n = 5), and 20‐day–stored (n = 5) platelets and obtained samples for in vitro testing at baseline and after the designated storage time. Twenty three units were available for in vitro testing. Five‐ and 7‐day (n = 5 each), room temperature (RT)‐stored platelets served as the current clinical standard control. RESULTS: In vivo, we found a continuous decline in platelet recovery from 5 to 20 days. Platelet survival reached a low nadir after 10 days of storage. Ex vivo, we observed the maximum platelet αIIbβ3 integrin response to collagen at 5 days of cold storage, and we saw a continuous decline thereafter. However, platelet integrin activation and mitochondrial membrane integrity were better preserved after 20 days at 4°C, compared to 5 days at RT. Platelet metabolic parameters suggest comparable results between 20‐day cold‐stored platelets and 5‐ or 7‐day RT‐stored platelets. CONCLUSION: In summary, we performed the first studies with extended, cold‐stored, apheresis platelets in plasma for up to 20 days with a fresh comparator. Storing cold‐stored platelets up to 20 days yields better results in vitro, but further studies in actively bleeding patients are needed to determine the best compromise between hemostatic efficacy and storage prolongation.